Implementation of Regional Development Information System (SIPD) in Increasing Coordination of Regional Development - frans dione (Jurnal Kebijakan Pemerintahan, 2020)
The success of the development is determined by the coordination between the central and regional governments, coordination that needs to be supported by accurate information. The main objective of this research is to study and discuss how to implement the Regional Development Information System (SIPD) in enhancing regional development coordination, in addition to studying and discussing what supports SIPD implementation in increasing regional development in Bengkulu City. This research method is descriptive qualitative with an inductive discussion. Data collected through observation, interviews, and documentation. Data were analyzed through data reduction, data presentation, and conclusion concluded. The results showed that the implementation of the Regional Development Information System (SIPD) was in accordance with applicable regulations. SIPD on SIPD implementation on SIPD implementation which can be seen from the level of SIPD representation in Bengkulu city. In addition, there are not yet maximum implementing regulations related to licensing for the person in charge of SIPD to increase the level of licensing in data filling. Suggestions from this research include the need for the Mayor's commitment to implementing the SIPD program. The City Government needs to approve regulations related to government regulations for Agency Agencies that do not support the SIPD program.